(untitled) - Herren, Ray V. (Australia, 2004)
Exploring Agriscience, third edition, is a middle school text for students in Agricultural Education Programs who are enrolled in their first agriculture or agriscience class. Contents center on an exploration of agricultural industry as well as an explanation of how science concepts are used in agriculture. Topics covered include The history of agriculture; Soils, Plant structures; Entomology; Floriculture; Nursery and Landscaping; Fruit and Nuts; Row crops; Forestry; The Environment; Organic agriculture; Animal Science (including Dairy and Poultry); Aquaculture; Companion Animals; Ethics; Biotechnology; Careers; Agricultural Mechanics; Food Science; and Agricultural Education Programs. The text is illustrated with full color images that help clarify text material. Each chapter contains an insert that provides a description of an FFA Career Development Event (CDE) that relate directly to the chapter topic. Each chapter contains student learning activities that help students relate the text concepts to real life. In addition, each chapter ends with True/False, Multiple Choice and discussion questions to help evaluate student learning. An extensive teaching/learning package for the text is available. This package includes an instructor's guide, a lab model, and a classmaster CD-ROM that contains transparency masters, lesson plans, and a computerized test bank
Keywords: Agriculture,Agriculture; Juvenile literature; United States